2019
DOI: 10.4062/biomolther.2019.063
|View full text |Cite
|
Sign up to set email alerts
|

G0/G1 Switch 2 Induces Cell Survival and Metastasis through Integrin-Mediated Signal Transduction in Human Invasive Breast Cancer Cells

Abstract: Human breast cancer cell line, MDA-MB-231, is highly invasive and aggressive, compared to less invasive cell line, MCF-7. To explore the genes that might influence the malignancy of MDA-MB-231, DNA microarray analysis was performed. The results showed that G0/G1 switch 2 (G0S2) was one of the most highly expressed genes among the genes upregulated in MDA-MB-231. Although G0S2 acts as a direct inhibitor of adipose triglyceride lipase, action of G0S2 in cancer progression is not yet understood. To investigate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…G0/S2 switch protein (BT20 high expression, MCF7 low expression associated with WWOX silencing and E2) mediates the Hippo pathway and induces EMT. Silencing decreased cell proliferation, migration, and invasion of MDA-MB-231 cells (Cho et al 2019). Another protein ANXA1 (downregulated in MC7 and BT20 E2 treated and WWOX-depleted cells) which was previously reported to regulate EMT and is associated with highly invasive basallike breast cancer phenotype (Graauw et al 2010) was found also to contribute to trastuzumab resistance through AKT activation (Berns et al 2016;Sonnenblick et al 2015).…”
Section: Wwox and Tgfα And Tgfβmentioning
confidence: 80%
“…G0/S2 switch protein (BT20 high expression, MCF7 low expression associated with WWOX silencing and E2) mediates the Hippo pathway and induces EMT. Silencing decreased cell proliferation, migration, and invasion of MDA-MB-231 cells (Cho et al 2019). Another protein ANXA1 (downregulated in MC7 and BT20 E2 treated and WWOX-depleted cells) which was previously reported to regulate EMT and is associated with highly invasive basallike breast cancer phenotype (Graauw et al 2010) was found also to contribute to trastuzumab resistance through AKT activation (Berns et al 2016;Sonnenblick et al 2015).…”
Section: Wwox and Tgfα And Tgfβmentioning
confidence: 80%
“…For example, CSF3 (AKA granulocyte colony-stimulating factor AKA G-CSF) has been shown to act through multiple methods to enhance breast cancer metastasis, such as the induction of granulocytic myeloid-derived suppressor cells which subsequently reduce T cell activation and proliferation or through the direct activation of H-Ras oncogene, MAPK, ERK1/2, and AKT signaling pathways 51 . Similarly, mechanisms by which the top upregulated genes G0S2 52 , COL7A1 53 , IL16 54 , and DNER 55 enhance breast cancer metastasis or seeding have all been independently verified, while increased expression of SAA2 56 and C15orf48 57 have been associated with poorer prognosis in breast cancers. On the other hand, loss of F1 and F2 downregulated genes such as SUSD2 has been linked to enhanced ovarian cancer metastasis in preclinical mouse models 58 .…”
Section: Discussionmentioning
confidence: 92%
“…This influence could be relevant for the metabolic adaptation of cancer cells. However, preliminary studies have provided conflicting data on a role of G0S2 in cancer cells [34,[52][53][54]. Our discovery about the existence of strong correlations between G0S2 levels and patients' survival in different cancers suggests the needing of a more extensive investigation about the impact of this gene on the metabolism and proliferation of transformed cells.…”
Section: Discussionmentioning
confidence: 99%